Changes in body weight and healthy lifestyle perception of Indonesian adults during COVID-19 pandemic - Septiyana, Sorra Milwayani; Aji, Arif Sabta; Paratmanitya, Yhona (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Social restrictions during the COVID-19 pandemic have impacted eating patterns and psychological status, leading to changes in body weight and perceptions of a healthy lifestyle in society. This study aimed to investigate the effect of social restrictions on weight changes and perceptions of a healthy lifestyle in adults during the COVID-19 pandemic in Indonesia. METHODS This cross-sectional study was conducted using convenience sampling on 287 Indonesian adults from June to August 2020. The data were collected using a self-administered online questionnaire using Google Forms. Data were analyzed using the chi-square test and logistic regression analysis. RESULTS There was no effect of social restrictions on weight changes and perceptions of lifestyle in adults (p = 0.900 and 0.748, respectively). However, 112 respondents (78.3%) had positive perceptions or supported adopting a healthy lifestyle under large-scale social restrictions. Multivariable logistic regression demonstrated that adults aged 36–45 years had a 3.6 times higher risk of weight changes than young adults aged 25–35 years (p = 0.004, OR = 3.65, 95% CI = 1.51–8.85). CONCLUSIONS Social restrictions did not affect weight changes and perceptions of a healthy lifestyle in adults during the COVID-19 pandemic in Indonesia. However, older adults might have a higher risk of body weight changes. Controlling body weight is important to prevent further weight gain and the risk of noncommunicable diseases that can aggravate COVID-19.